A novel approach to regulate glucose uptake in an anaplastic thyroid cancer cell line - Shabnam Heydarzadeh; Ali Asghar Moshtaghie; Maryam Daneshpour; Mehdi Hedayati (Endocrine Connections)
Aims and background: Curcumin’s function in affecting cancer metabolic reprogramming remains poorly understood. Herein, we aimed to elucidate a novel link between curcumin and the glucose uptake metabolism and the status of glucose transporters (GLUTs) in the SW1736 cell line derived from anaplastic thyroid cancer. Materials and methods: The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test and flow cytometry were employed to test cell viability and cell death. For glucose uptake detection, the ‘glucose oxidase/peroxidase 4-aminoantipyrine’ enzymatic colorimetric assay was applied to measure the direct glucose levels inside the cells. Determination of GLUT1 and GLUT3 mRNA and protein expression in SW1736 cells was performed by qRT-PCR and western blotting. In addition, the scratch wound healing assay was conducted for cell migration. Results: The data indicated that curcumin-induced cell death is independent of apoptosis in this type of thyroid cancer cell line. Furthermore, significantly reduced GLUT1 and GLUT3 expression was observed after treatment with curcumin, resulting in the inhibition of glucose uptake (P < 0.05). Scratch assay indicated the inhibition of cell migration in SW1736 cells treated with curcumin (P < 0.05). Conclusion: It can be concluded that GLUTs, as metabolic targets, can be blocked specifically by curcumin for thyroid cancer prevention. Curcumin, as a promising anti-cancer agent, inhibits the growth of SW1736 anaplastic thyroid cancer cells by regulating the glucose uptake pathway and cell death. Altogether, these results suggest that the glucose pathway may be an essential target for therapeutic intervention to sensitize tumor cells to the cell death process by inhibition of glucose transporters. Statement of translational relevance: As described in our previously published article, ‘Regulators of glucose uptake in thyroid cancer cell lines’, non-oncogene addiction is one of the recent principles of cancer therapy. Moreover, herein, for the first time, we decided to investigate the anti-thyroid cancer effects of a bioactive phytochemical and establish a signaling link between curcumin and the glucose uptake metabolism of anaplastic thyroid cancer cells. This title covers the entire range of the biological sciences, and we attempt to fill the gaps between cell biology, medicine, cancer and plant knowledge. The influence of cancer on human society is indescribable. Human studies are often contradictory around the effects of polyphenols against cancer. We believe that it is important to draw boundaries between the usages of polyphenols in cancer prevention versus cancer treatment. We anticipate that this study’s findings will contribute to a better understanding of the mechanism underlying curcumin’s anti-cancer properties, providing a theoretical foundation for the future clinical application of curcumin-related medications.